IMPACT OF SENSOR DATA SAMPLING RATE IN GNSS/INS INTEGRATED NAVIGATION WITH VARIOUS SENSOR GRADES - Y. Wei; Y. Li; Y. Li (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
The fast-growing small-size equipment requires robust navigation with low power consumption and high positioning accuracy. However, as the mainstream robust navigation method against different environments, GNSS/INS causes excessive power dissipation. Considering downsampling is confirmed as a simple but efficient way to reduce energy usage, this paper focuses on the impact of sensor data sampling rate in GNSS/INS integrated navigation to give guidance for selecting proper GNSS/INS rates. Specifically, we first simulated data sequences with various sensor grades and then downsampled them into multiple sampling rates, followed by positioning accuracy evaluation. Experiment results have shown that GNSS interval caused more significant degradation of the navigation accuracy than the IMU rate. Meanwhile, the 5 sec GNSS interval with the 20 Hz IMU rate may be the most suitable for a power-accuracy trade-off solution in our experiments, which has a 16% reduction in positioning accuracy compared to the standard sampling rate combination (i.e, 1 sec GNSS interval and 200 Hz IMU sampling rate).